Conservation Agriculture and its contribution to the achievement of agri-environmental and economic challenges in Europe - González-Sánchez, E. (2017)
Conservation Agriculture is an ecosystem approach to farming capable of providing solutions for numerous of the agri-environmental concerns in Europe. Certainly, most of the challenges addressed in the Common Agriculture Policy (CAP) could be tackled through Conservation Agriculture (CA). Not only the agri-environmental ones, but also those concerning farmer and rural communities’ prosperity. The optimisation of inputs and similar yields than conventional tillage, make Conservation Agriculture a profitable system compared to the tillage based agriculture. Whereas this sustainable agricultural system was conceived for protecting agrarian soils from its degradation, the numerous collateral benefits that emanate from soil conservation, i.e., climate change mitigation and adaptation, have raised Conservation Agriculture as one of the global emerging agrosciences, being adopted by an increasing number of farmers worldwide, including Europe.